Three phylogenetically distinct and culturable diazotrophs are perennial symbionts of leaf-cutting ants - Zani, Renata de Oliveira Aquino [UNESP]; Ferro, Milene [UNESP]; Bacci, Maurício [UNESP] (Wiley, 2021)
The obligate mutualistic basidiomycete fungus, Leucocoprinus gongylophorus, mediates nutrition of leaf-cutting ants with carbons from vegetal matter. In addition, diazotrophic Enterobacteriales in the fungus garden and intestinal Rhizobiales supposedly mediate assimilation of atmospheric nitrogen, and Entomoplasmatales in the genus Mesoplasma, as well as other yet unidentified strains, supposedly mediate ant assimilation of other compounds from vegetal matter, such as citrate, fructose, and amino acids. Together, these nutritional partners would support the production of high yields of leafcutter biomass. In the present investigation, we propose that three phylogenetically distinct and culturable diazotrophs in the genera Ralstonia, Methylobacterium, and Pseudomonas integrate this symbiotic nutrition network, facilitating ant nutrition on nitrogen. Strains in these genera were often isolated and directly sequenced in 16S rRNA libraries from the ant abdomen, together with the nondiazotrophs Acinetobacter and Brachybacterium. These five isolates were underrepresented in libraries, suggesting that none of them is dominant in vivo. Libraries have been dominated by four uncultured Rhizobiales strains in the genera Liberibacter, Terasakiella, and Bartonella and, only in Acromyrmex ants, by the Entomoplasmatales in the genus Mesoplasma. Acromyrmex also presented small amounts of two other uncultured Entomoplasmatales strains, Entomoplasma and Spiroplasma. The absence of Entomoplasmatales in Atta workers implicates that the association with these bacteria is not mandatory for ant biomass production. Most of the strains that we detected in South American ants were genetically similar with strains previously described in association with leafcutters from Central and North America, indicating wide geographic dispersion, and suggesting fixed ecological services.